Asosiasi Keragaman Lokus DNA Mikrosatelit DRB3 Gen Bola dengan Berat Badan Induk dan Berat Lahir Pedet pada Sapi Bali - Ni Nyoman Trinayani; I Nengah Wandia; I Ketut Puja (Veterinary Science and Medicine Journal, 2013)
Genomic selection has a high potency to improve the genetic quality of Bali cattle. In effort to find out a molecular marker or DNA segment which is linked with a certain phenotype, we examined the association between BoLa-DRB3 microsatellite polymorphism and dam body weight and birth weight of calves in Bali cattle. A total of 40 dams from Abuan Village, the District of Susut was investigated. The total DNA was extracted with QIAamp DNA blood mini kit. The locus was amplified using PCR technique with a 54OC annealing temperature.. Alleles were separated through PAGE 6%, and visualized with silver staining. We found 10 alleles which their length varied from 145 bp to 233 bp. Allele 195 had the highest frequency that was 35.0%. The HE, HO, PIC were 0.821, 0.875, and 0.791 consecutively. Statistical analysis showed that the polymorphism of DRB3 microsatellite had a marginally significant association (p < 0.1) to the dam body weight. However, it had no significant association to the birth weight of the calves. The results of the research reflect that the DRB3-BoLA gene has a weak potency in controlling the body weight.